The Role of AI-Based Chatbots in Supporting Biology Education Students’ Learning - Wahyuni, Ayu; Junaidi, Agus; Mansur; Sriadhi; Halimatun, Futria (Journal Of Biology Education Research (JBER), 2025)
The development of Artificial Intelligence (AI) technology continues to make a significant contribution to the field of education, particularly through the use of chatbots as virtual learning assistants. AI-based chatbots can help students overcome learning difficulties, whether in understanding material, increasing motivation, or providing guidance tailored to individual needs. This study aims to analyze the effectiveness of AI-based chatbots in enhancing Biology Education students’ understanding and ability to overcome learning difficulties in the digital learning environment. This study uses a quantitative survey method, involving 60 respondents from the Biology Education Study Program at a state university in Indonesia. The population in this study consists of all students in the Biology Education Study Program who have used AI chatbots as learning tools. The sampling technique used is purposive sampling, with the criteria being students who have used AI chatbots for at least one semester in their learning activities. Data were collected using a structured questionnaire based on five indicators: ease of access, clarity of material explanation, learning motivation, effectiveness of feedback, and contribution to conceptual understanding. The results of the study show that students consider AI chatbots to be effective learning tools, especially in providing instant feedback, clear explanations, and improving their understanding of basic and complex biological concepts. Most students showed a high level of acceptance of chatbots. The students appreciated its accessibility, clarity, and relevance of responses. The analysis also shows that chatbots serve as facilitators of independent learning, which strengthens motivation, increases confidence, and deepens conceptual understanding. However, this study also found that the effectiveness of chatbots still needs improvement, especially in providing more contextual explanations and supporting higher-order cognitive skills such as analysis and synthesis. In conclusion, students rated the AI chatbot as an effective learning tool because it provides instant feedback, clear explanations, and improves their understanding of biological concepts. The chatbot also supports independent learning, motivation, and confidence. However, its effectiveness still needs to be improved, especially in providing contextual explanations and supporting higher-order cognitive skills.